Leptin Modulates the mRNA Expression of Follicle Development Markers in Post-hatch Chicks in an Age-Dependent Manner - Shaikat, Amir Hossan; Ochiai, Masami; Sasaki, Akari; Takeda, Misa; Arima, Akari; Ohkubo, Takeshi (Frontiers in Physiology, 2021)
Leptin is involved in regulating reproductive function in chickens and leptin system development initiates during the early embryonic stage; however, whether leptin has a specific role in regulating ovarian development is still not fully understood. The present study investigated the expression of ovarian functional markers in growing juvenile chickens, along with leptin’s effects on gene expression in the hypothalamus-pituitary-gonadal (HPG) axis on specific ovarian remodelling days. Leptin receptor (LEPR), follicular stimulating hormone receptor (FSHR), and CYP19A1 mRNA expression tended to increase with age in the ovaries of growing chicks. In the 7-day-old ovary, intraperitoneally injected leptin significantly increased LEPR, FSHR, and CYP19A1 mRNA expression, and this resulted in increased serum oestradiol levels. However, leptin had no effect on hypothalamic LEPR, gonadotropin-releasing hormone 1 (GnRH1), or gonadotropin-inhibitory hormone (GnIH) mRNAs; however, in the pituitary gland, leptin significantly increased luteinizing hormone beta subunit ( mRNA expression, but had no effect for follicle-stimulating hormone beta subunit (FSHB mRNA expression. In 28-day-old chicks, hypothalamic and pituitary mRNAs were unaffected by leptin administration, except hypothalamic LEPR mRNA that was upregulated by a high dose of leptin. In the ovary, Leptin dose-dependently decreased LEPR mRNA expression; low doses of leptin significantly increased FSHR mRNA expression, whereas high doses significantly decreased this expression; leptin did not affect CYP19A1 mRNA expression; and high leptin doses reduced serum oestradiol levels significantly. Collectively, these results suggest that leptin modulates directly early folicle development in juvenile chickens on the specific ovarian remodelling days.